Effects of fresh and digested cowdung and poultry litter on the growth and yield of cabbage (Brassica oleracea) (Bangladesh Journal of Scientific and Industrial Research, 2013)
A field experiment was conducted during Rabi season in the experimental field of BCSIR to see the effects of fresh and digested cowdung (CD) and poultry litter (PL) bio-slurry on the growth and yield of cabbage (Brassica oleracea). The experiment was laid in a Randomized Complete Block Design (CRBD) with six different treatments including control. Cabbage variety Atlas-70 was transplanted at the age of 35 days and was harvested at 120 days. Plant height, circumference, marketable weights and whole plant weight were examined to perceive the effects on the growth and yield of cabbages. The experiment revealed that both digested PL and CD bio-slurry had a significant effect (P < 0.01) on the growth and yield components of cabbage. Increased plant growth and yield were in the order of digested PL bio-slurry > digested CD bio-slurry > fresh PL > fresh CD in combination with recommended dose of fertilizers (RDF). Among the treatments, the highest head yield of cabbage (97.6 t ha-1) was obtained from RDF + 5 t ha-1 digested PL bio-slurry which was 366 % higher than the control. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15382 Bangladesh J. Sci. Ind. Res. 48(1), 1-6, 2013